DO THE MEDICAL RECORD ARCHIVES IN ACCORDANCE WITH ABOUT CRITERIA OF MEDICAL RECORD SERVICES? - Elif DİKMETAŞ YARDAN (Fırat University, 2019)
Information in health care reflects to records. Patient files is heart of hospital. Correct and complete patient records valid. Confidentiality and privacy of medical records are very important. Medical records are legal documents, that are used in clinical and administrative information systems. It is important for hospital efficiency. Medical records can be electronic and paper. Paper records were collected in medical record archives. In this study, "do the unversity hospital has got criteria of medical record?" question was answered. In this study, a university hospital in Turkey was examined appropriateness criteria about medical record services by Türk Standartlar Enstitüsü in April 1997. This study was done with medical record archives manager and other informed people’s interview and observation in 2015. This study was examined main headings that criteria related medical records services, goals and objectives, organization and management, executive and team, facilities, equipment and materials, policies and procedures, criteria relevant medical records, the content of medical records, medical records format, combining and indexing, medical records control, complete of registration and statistical relevance. In the result of study, was found that criteria about medical record services wasn’t done completely. Hospital and medical record archives management must examine and complete missing criteria by hospital and archive management.